ACTIVATION OF HUMAN FIBROBLASTS BY CHRONIC RADIATION RATHER THAN ACUTE RADIATION. Issue 13 (9th September 2022) - Shimura, T; Zaharieva, E; Sasatani, M; Kawai, H; Kamiya, K; Ushiyama, A
Abstract: Cancer-associated fibroblast (CAF), an activated type of fibroblast, is a major stromal cell that contributes to tumor initiation and development in the tumor microenvironment (TME). We previously reported that fractionated radiation rather than acute radiation causes progressive damage to mitochondria and increases the generation of reactive oxygen species, playing an important role in the fibroblast activation in normal tissue injury. Activated fibroblasts then become CAF by interacting with tumor cells, promoting tumor growth in vivo. We here examined the chronic radiation effect on fibroblast activation. Acute radiation (<2.5 Gy) did not increase alpha-Smooth muscle actin, a CAF marker expression in healthy human cells, whereas chronic radiation (2.5 Gy) did. It can be concluded that the induction of fibroblast activation changes across acute radiation, fractionated radiation, and chronic radiation depending on the irradiation technique. This study highlights that radiation activates fibroblasts, playing a role in radiation-related tumor development via TME formation.